2022
DOI: 10.1111/ajo.13587
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes and awareness of Australian women regarding peripartum antibiotic use: A multicentre survey

Abstract: Background: Peripartum antibiotics are commonly administered. Little is known of the attitudes of pregnant women toward peripartum antibiotics. Aim:We aimed to assess the awareness of and attitudes toward peripartum antibiotic use in Australian women. Materials and Methods:We surveyed post-partum women at three hospitals over six months. Women reported if they received antibiotics 48 h either side of delivery and responded to statements assessing attitudes to peripartum antibiotic use. Administered antibiotics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…37 Communicating the potential risks of pre-incision antibiotics to patients is challenging, given it is now considered the standard of care. Pregnant women are likely to be broadly aware of the potential side effects of antibiotics, 38 and when surveyed, a majority indicated that they would prefer to receive antibiotics after cord clamping, stating that they did not think the risk of getting an infection themselves was convincing enough to risk short-or long-term complications to their baby. 39 Table 1 shows the known risk factors for post-cesarean surgical site infection.…”
Section: Antib Iotic Prophyl a Xis For Ce Sare An S Ec Ti On: Current...mentioning
confidence: 99%
“…37 Communicating the potential risks of pre-incision antibiotics to patients is challenging, given it is now considered the standard of care. Pregnant women are likely to be broadly aware of the potential side effects of antibiotics, 38 and when surveyed, a majority indicated that they would prefer to receive antibiotics after cord clamping, stating that they did not think the risk of getting an infection themselves was convincing enough to risk short-or long-term complications to their baby. 39 Table 1 shows the known risk factors for post-cesarean surgical site infection.…”
Section: Antib Iotic Prophyl a Xis For Ce Sare An S Ec Ti On: Current...mentioning
confidence: 99%